The authority of the Security Council to refer to the International Criminal Court - الزيتي علي; غسان علي; صفاء جابر جنيدي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The granting of wide powers to the Security Council within the Rome Statute led to the reservation of many countries and international organizations due to the latter’s fear of the reflection of the political considerations of the members of the Security Council on its exercise of the referral power to the court, and the lack of cooperation of states with the International Criminal Court after the referral is the main obstacle limiting of its effectiveness, and without the Security Council it cannot take repressive measures to force these countries to cooperate with it. These powers established by the Security Council in Article 13 of the Rome Statute effectively assist and activate the court’s jurisdiction.